2020
DOI: 10.1002/uog.21974
|View full text |Cite
|
Sign up to set email alerts
|

Role of prenatal magnetic resonance imaging in fetuses with isolated mild or moderate ventriculomegaly in the era of neurosonography: international multicenter study

Abstract: Objectives To assess the role of fetal magnetic resonance imaging (MRI) in detecting associated anomalies in fetuses presenting with mild or moderate isolated ventriculomegaly (VM) undergoing multiplanar ultrasound evaluation of the fetal brain. Methods This was a multicenter, retrospective, cohort study involving 15 referral fetal medicine centers in Italy, the UK and Spain. Inclusion criteria were fetuses affected by isolated mild (ventricular atrial diameter, 10.0–11.9 mm) or moderate (ventricular atrial di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…The results from this study support our previous findings on the diagnostic accuracy of neurosonography in isolated mild and moderate ventriculomegaly, 9,10 further highlighting the need for a detailed multiplanar assessment of fetal brain, as suggested by ISUOG 2007 guidelines, in the case of a suspected CNS structural defect. 11,39 Despite this, undetected anomalies at ultrasound TA B L E 5 Pooled proportions for the rate of different additional anomalies detected only at MRI in fetuses with isolated complete and partial ACC…”
supporting
confidence: 89%
See 2 more Smart Citations
“…The results from this study support our previous findings on the diagnostic accuracy of neurosonography in isolated mild and moderate ventriculomegaly, 9,10 further highlighting the need for a detailed multiplanar assessment of fetal brain, as suggested by ISUOG 2007 guidelines, in the case of a suspected CNS structural defect. 11,39 Despite this, undetected anomalies at ultrasound TA B L E 5 Pooled proportions for the rate of different additional anomalies detected only at MRI in fetuses with isolated complete and partial ACC…”
supporting
confidence: 89%
“…previously reported when a state-of-the-art multiplanar assessment of the fetal brain (neurosonogram) was performed. [9][10][11] The primary aim of this systematic review was to report on the role of fetal MRI in detecting additional anomalies in fetuses with isolated ACC on ultrasound. The secondary aim was to elucidate the rate of additional anomalies detected at MRI according to gestational age at scan and type of ultrasound assessment performed (standard vs dedicated neurosonography).…”
Section: Key Messagementioning
confidence: 99%
See 1 more Smart Citation
“…There is a limited number of publications on the contribution of fetal MR to the gestational termination. In the review of Di Mascio et al, [30] the rate of gestational termination request after standard sonography was 5.1% while it was 2.9% after the fetal MR which was added later. Similar to our study, it can be concluded that we need to investigate other factors rather than the diagnosis type in terms of convincing patients.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that maternal body mass index (BMI), the cases with medium-severe level ventriculomegaly more than mild ventriculomegaly and fetal MR conducted after 24 weeks of gestation were among the factors affecting the detection of additional anomaly. [29,30] Although the fetal MR conducted before 24 weeks of gestation also performs well, the cortical and white matter anomalies and intracranial hemorrhage diagnoses were the diagnosis groups which made fetal MR superior at the third trimester. [28,29] According to the literature data, prognosis cannot be predicted in pCCA cases due to the uncertainty of antenatal, postnatal and newborn processes.…”
Section: Discussionmentioning
confidence: 99%